THE IMPORTANCE OF CHILDREN’S LITERATURE FOR THE TRAINING OF STUDENT READERS - Kaene da Silva Cabral, Vládia (Revista Gênero e Interdisciplinaridade, 2023)
this article is the result of a bibliographical and qualitative research and it is proposed to present some reflections on the importance of Child Literature for the development of the language and orality of the child from reading practices and how it can be an opening tool for the their intellectual development and a path to the universe of reading. Reading and bibliographical research on literary literacy and children’s literature have become reflexive axes for the construction of the research corpus composed of two works of the Literacy Program in the Right Age (PAIC). Thus, the analyzes show that reading practices in Children’s Literature are crucial for expanding vocabulary, productions of good oral texts, the taste for reading, critical thinking and gives the child the discovery, the imagination and the creation of the self and the world around you.